Input-to-State Stability of Nonlinear Switched Systems via Lyapunov Method Involving Indefinite Derivative - Peng Li; Xiaodi Li; Jinde Cao (Complexity)
This paper studies the input-to-state stability (ISS) of nonlinear switched systems. By using Lyapunov method involving indefinite derivative and average dwell-time (ADT) method, some sufficient conditions for ISS are obtained. In our approach, the time-derivative of the Lyapunov function is not necessarily negative definite and that allows wider applications than existing results in the literature. Examples are provided to illustrate the applications and advantages of our general results and the proposed approach.